Wishful Thinking versus Reality: High-growth Aspirations of Start-ups and Established Entrepreneurs in ASEAN - Guelich, Ulrike (Asian Academy of Management Journal, 2020)
Most enterprises in the Association of Southeast Asian Nations (ASEAN) are micro and small enterprises. Few have aspirations to “dream big.” From an economic perspective, high-growth firms provide many benefits. This empirical study explores both country-level contextual factors such as country competitiveness or innovativeness and individual-level factors associated with high-growth, such as an entrepreneur’s market expansion plans, new product perceptions, export orientation and use of latest technologies. In this context, we investigate whether to “dream big” is associated with specific strategic intentions and which influencing factors hinder or foster aspirations to grow the business by more than 20 employees within five years while developing it into an established business. Utilising random sampling of data in six ASEAN countries, collected in the years 2013 to 2015 and comparing male to female entrepreneurs, the regression results of this empirical study show that although high growth-oriented entrepreneurs in both start-ups and established enterprises account for only 2.7% of all enterprises in this study, high-growth aspirations can only partially be sustained by early-stage entrepreneurs into the next business phase since it depends on several factors: (1) receiving funding (for both genders); (2) being export oriented (for male entrepreneurs); and (3) perceptions of having new products or services to offer to the market (for women entrepreneurs). Both genders are less prone to pursue their initial early-stage growth goals as established entrepreneurs. We infer that established entrepreneurs gain more clarity on the deployment of growth through implementation in the organisation while running their businesses and therefore may be more realistic in their predictions or less confident in their pursuit of ambitious goals.